A new scenario of bioprospecting of Hymenoptera venoms through proteomic approach - Santos, L. D. [UNESP]; Pieroni, M.; Menegasso, A. R. S. [UNESP]; Pinto, J. R. A. S. [UNESP]; Palma, Mario Sergio [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Venoms represent a huge and essentially unexplored reservoir of bioactive components that may cure diseases that do not respond to currently available therapies. This review select advances reported in the literature from 2000 to the present about the new scenario of Hymenoptera venom composition. on account of new technologies in the proteomic approach, which presents high resolution and sensitivity, the combination of developments in new instruments, fragmentation methods, strategic analysis, and mass spectrometry have become indispensable tools for interrogation of protein expression, molecule interaction, and post-translational modifications. Thus, the biochemical characterization of Hymenoptera venom has become a major subject of research in the area of allergy and immunology, in which proteomics has been an excellent alternative to assist the development of more specific extracts for diagnosis and treatment of hypersensitive patients to Hymenoptera venoms.
Keywords: hymenoptera; venoms; allergens; phospholipase A1; wasp venom antigen 5; hyaluronoglucosaminidase; mass spectrometry; proteomics